KONSEP BELAJAR PENDIDIKAN ISLAM DALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Asif Az-Zhafi, Ghea Silviana Putri, (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2020)
ABSTRACTLearning is the basis of key to education, without learning education does not mean anything. Education in Islam is a process that involves complete people , including the rational, spiritual, and social dimensions, all intertwined integrated perceptual and relying, fully, in fundamental and morality on the Qur’an and Hadith. Through Islamic Education, individuals are educated and hijacked to follow all-encompassing methods which involve all methods that cover all spect needed, witout borrowing anything, or giving an edge over the others. Al-Qur’an and Hadith of the prophet. Associated intensilvey for individuals and osciety and the main source of knowledge. Learning is an activity that processing using non-fundamental very basic in the implementation of eachtype and level of education.Keyword: Concept Learning, Islamic Education, Al-Qur’an and Hadits